Efficient learning strategies: Student attraction to entrepreneurship lessons using technology - Azmy Ramelan Kurniawan; Sistiyani Sistiyani; Zalfa Feyza Qolbi (Universitas Pendidikan Indonesia, 2024)
Education is an essential foundation in shaping the future of individuals and the progress of a country. However, the education system often faces challenges in effectively meeting learners' needs, mainly due to monotonous learning methods and a mismatch with individual learning styles. In addition, increasing learning productivity is a primary goal in education. ICT integration is the key to improving the quality of learning. Thus, this research combines learning styles, ICT integration, and strategies to improve learning productivity to create effective and relevant education. This research uses a descriptive approach with data collection techniques in the form of questionnaires. The collected data were analyzed to understand various aspects related to learning styles, ICT integration, and learning productivity strategies. This research shows that learning strategies are crucial in educational services to increase understanding and effective student learning applications. In addition, using technology in entrepreneurship learning can increase students' interest in learning and experience. Abstrak Pendidikan adalah fondasi penting dalam membentuk masa depan individu dan kemajuan sebuah negara. Namun, sistem pendidikan sering menghadapi tantangan dalam memenuhi kebutuhan peserta didik secara efektif, terutama karena metode pembelajaran yang monoton dan ketidaksesuaian dengan gaya belajar individu. Dengan demikian, penelitian ini bertujuan untuk mengintegrasikan konsep gaya belajar, pemanfaatan Teknologi Informasi dan Komunikasi (TIK), serta strategi pembelajaran guna meningkatkan produktivitas belajar, dengan tujuan menciptakan pendidikan yang efektif dan relevan. Penelitian ini menggunakan pendekatan deskriptif dengan teknik pengumpulan data berupa kuesioner. Data yang terkumpul dianalisis untuk memahami berbagai aspek yang terkait dengan gaya belajar, integrasi TIK, dan strategi produktivitas belajar. Hasil dari penelitian ini menunjukkan bahwa strategi pembelajaran merupakan elemen kunci dalam layanan pendidikan, dengan tujuan meningkatkan pemahaman dan penerapan belajar secara efektif pada peserta didik. Selain itu, penggunaan teknologi dalam pembelajaran kewirausahaan dapat meningkatkan minat belajar dan pemahaman peserta didik. Kata Kunci: Efisiensi; kewirausahaan; strategi belajar; teknologi pembelajaran